Balancing obligations: should written information about life-sustaining treatment be neutral?. Issue 3 (24th April 2014) - Xafis, Vicki; Wilkinson, Dominic; Gillam, Lynn; Sullivan, Jane
Abstract : Parents who are facing decisions about life-sustaining treatment for their seriously ill or dying child are supported by their child's doctors and nurses. They also frequently seek other information sources to help them deal with the medical and ethical questions that arise. This might include written or web-based information. As part of a project involving the development of such a resource to support parents facing difficult decisions, some ethical questions emerged. Should this information be presented in a strictly neutral fashion? Is it problematic if narratives, arguments or perspectives appear to favour stopping over continuing life-sustaining treatment? Similar questions might arise with written materials about decisions for adults, or for other ethically contentious decisions. This paper explores the meaning of 'balance' in information provision, focusing particularly on written information about life-sustaining treatment for children. We contrast the norm of non-directiveness in genetic counselling with the shared decision-making model often endorsed in end-of-life care. We review evidence that parents do not find neutrality from medical professionals helpful in discussions. We argue that balance in written information must be understood in the light of the aim of the document, the most common situation in which it will be used, and any existing biases. We conclude with four important strategies for ensuring that non-neutral information is nevertheless ethically appropriate.